2003
DOI: 10.1210/rp.58.1.325
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis and Identification of Novel Molecules Involved in Insulin-like Growth Factor-1 Receptor Signaling and Gene Expression

Abstract: The insulin receptor (IR) and the insulin-like growth factor-1 receptor (IGF-1R) are members of the same subfamily of receptor tyrosine kinases. The two receptors phosphorylate many of the same substrates and activate the same signaling modules, including the mitogen-activated protein kinase (MAPK) and phosphatidyl inositol 3Ј kinase (PI3K) signaling pathways. Although the IR and IGF-1R share some redundant functions in metabolism, cell growth, differentiation, and apoptosis, they also exhibit distinct physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 74 publications
(33 reference statements)
2
39
0
1
Order By: Relevance
“…Table 1 in bold) and PPAP2A, which were preferentially up-and downregulated by ErbB2Ab, respectively, were also confirmed by QRT-PCR as being specific to ErbB2 activation ( Figure 3 Fambrough et al (1999) indicated that activation of platelet-derived growth factor receptor (PDGFR), fibroblast growth factor receptor, or EGFR resulted in nearly identical patterns of gene regulation. More recently, it has been shown that insulin receptor and insulin-like growth factor receptor-1 regulate an overlapping but distinct group of genes (Dupont et al, 2001(Dupont et al, , 2003Mulligan et al, 2002). Similar results have now been observed between TGFb receptors, ALK1 and ALK5, and two isoforms of the progesterone receptor (Ota et al, 2002;Richer et al, 2002).…”
Section: Validation Of Microarray Resultssupporting
confidence: 58%
“…Table 1 in bold) and PPAP2A, which were preferentially up-and downregulated by ErbB2Ab, respectively, were also confirmed by QRT-PCR as being specific to ErbB2 activation ( Figure 3 Fambrough et al (1999) indicated that activation of platelet-derived growth factor receptor (PDGFR), fibroblast growth factor receptor, or EGFR resulted in nearly identical patterns of gene regulation. More recently, it has been shown that insulin receptor and insulin-like growth factor receptor-1 regulate an overlapping but distinct group of genes (Dupont et al, 2001(Dupont et al, , 2003Mulligan et al, 2002). Similar results have now been observed between TGFb receptors, ALK1 and ALK5, and two isoforms of the progesterone receptor (Ota et al, 2002;Richer et al, 2002).…”
Section: Validation Of Microarray Resultssupporting
confidence: 58%
“…Even though cross-reaction can occur, each receptor binds to its own ligand with a 100-to 1000-fold higher affinity than that of the heterologous peptide. In agreement with these biochemical observations, IR and IGF1-R have certain shared functions, but also very distinct biological roles, and activate completely different sets of genes [40,79].…”
Section: Insulin/igf1 Receptors: a Signaling Pathway For The General supporting
confidence: 72%
“…The release of the large Nterminal domain allows subsequent γ cleavage, and liberation of Aβ and the signaling active intracellular domain of APP (AICD) (Figure 1). γ cleavage does not seem to be sequence specific and normally occurs either at position 40 or 42 of the Aβ region generating Aβ 40 and Aβ 42 , respectively. Release of Aβ in the extracellular milieu is followed by oligomerization and aggregation in the form of amyloid plaques.…”
Section: Ad Pathologymentioning
confidence: 98%
“…We identified 371 insulin-responsive genes that were specifically regulated in one compartment of the placenta. Some of the genes had also been identified in other microarray studies, which used different cell models, stimulation and analysis modalities [24][25][26][27][28], or by other methods [9,10], thus representing a robust insulin response common to many cell types.…”
Section: Discussionmentioning
confidence: 99%